The Effect of Temperature on the Synthesis of Nano-Gamma Alumina Using Hydrothermal Method - Mohammed, Abdul-Halim A.K.; Hussein, Hussein Q.; Mohammed, Mohammed Sabah (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Nano gamma alumina was prepared by double hydrolysis process using aluminum nitrate nano hydrate and sodium aluminate as an aluminum source, hydroxyle poly acid and CTAB (cetyltrimethylammonium bromide) as templates. Different crystallization temperatures (120, 140, 160, and 180) 0C and calcinations temperatures (500, 550, 600, and 650) 0C were applied. All the batches were prepared at PH equals to 9. XRD diffraction technique and infrared Fourier transform spectroscopy were used to investigate the phase formation and the optical properties of the nano gamma alumina. N2 adsorption-desorption (BET) was used to measure the surface area and pore volume of the prepared nano alumina, the particle size and the morphology of the surface of nano gamma alumina were estimated using AFM and SEM techniques ,respectively. All the samples represented pure nano gamma alumina with high crystalline and irregular hexagonal structure shape. The best results obtained were 456.5 m2/gm surface area, 0.49 cm3/gm pore volume, and 59.26 average particle size for the sample prepared at 180 0C crystallization temperature, and 500 0C calcinations temperature with nano spherical surface structure.